Violence and sexual and reproductive health service disruption among girls and young women during COVID-19 pandemic in Nepal: A cross-sectional study using interactive voice response survey. - Ashish Lamichhane; Shubheksha Rana; Krishna Shrestha; Rakshya Paudyal; Parash Malla; Shanti Upadhyaya; Durga Uprety; Julie Gurung; Elizabeth Satow (PLoS ONE)
Introduction There is a paucity of data on the impact of COVID-19 pandemic on girls and young women. The study examines the prevalence and correlates of violence and sexual and reproductive health (SRH) service disruption among girls and young women during COVID-19 restrictions and lockdown. Methods An interactive voice response survey was conducted among girls and women aged 18-24 years between 10th March to 24th April 2021. The survey enrolled 1314 participants. Descriptive analysis was used to assess prevalence of violence and SRH service disruption. Two sampled test of proportion was used to asses difference in prevalence of violence before and after the pandemic. Logistic regression was used to examine relationship between the outcome variables and socio demographic predictors. Results The study did not find significant difference in prevalence of violence before and after the pandemic. Education was found to be protective against experience of both physical and sexual violence after the pandemic. Dalit participants were four times more likely to report physical violence after the pandemic than Brahmin/Chhetri participants (OR:3.80; CI:1.41-10.24). Participants from 22-24-year age group were twice as likely to experience sexual violence compared to girls and participants from 18-21year age group (OR:2.25; CI:1.04-4.84). Participants from urban municipalities were 29% less likely to report SRH services disruption than participants from rural municipalities (OR-0.71, 95% CI: 0.55-0.91). Participants with disability were twice as likely to report disruption than participants without disability (OR-2.35, 95% CI: 1.45-3.82). Conclusions To reduce violence against girls and women due to the pandemic, interventions should focus on Dalit women and on preventing education discontinuation among girls and women. SRH service during the pandemic needs to be improved for girls and women with focus on girls and women from rural municipalities and girls and women with disability.